Принципи захисту культурної спадщини в умовах воєнного стану - Похиленко, Ірина (Констанц, 2024)
The armed aggression of Russia against Ukraine has caused significant destruction of cultural heritage objects. Protecting cultural heritage in times of war is a complex and responsible task that requires clear organization and coordinated efforts of state authorities, civil society organizations and the international community. Objective: To identify principles and measures for protecting cultural heritage in times of war. Results: The principles of protecting cultural heritage in times of war, as established in international law and national legislation, have been examined, the procedure for conducting various types of work on cultural heritage sites in times of war has been analyzed, the main scientific approaches to defining and preserving cultural heritage have been considered, principles and measures for protecting cultural heritage in times of war have been proposed. Conclusions: Protecting cultural heritage in times of war is a priority of state policy, The protection of cultural heritage should be based on principles of priority, comprehensiveness, legality and involvement of the public, Implementation of these principles involves assessing the state of cultural heritage, taking measures to protect and restore it.
The principles of cultural heritage protection in the conditions of martial law
Keywords: principles; cultural heritage; state of war; культурна спадщина; захист культурної спадщини; правове регулювання; російсько-українська війна; методи дослідження; 719"364"